The Effect of Science-Based Courses on Student Teachers' Biophilia Levels - Esra Ozay Kose; Seyda Gul; Abdurrahman Sefali (Journal of Science Learning, 2023)
This study examines the effect of science-based courses on student teachers' biophilia levels. Based on the quantitative research approach, this study was conducted using a quasi-experimental method. The sample of the study consists of 146 student teachers studying at the education faculty of a state university in the fall semester of the 2022-2023 academic year. The sample group was conducted with student teachers who chose four different science-based courses and voluntarily participated in the study. The Biophilia Scale with 25 items was used as a data collection tool. The findings showed that the biophilia levels of the participants in all four courses showed significant differences in favor of the post-tests. The findings also showed that the "environmental science" course's scale scores significantly differed from the other courses. In other words, the biophilia levels of student teachers who attended environmental science courses increased less than in the other courses. When the increase in biophilia level of student teachers according to their genders is examined, no difference was observed. As a result of the findings, it was suggested that more activities should be included in science-based lessons to increase students' biophilia levels.